Steroid 5α-Reductase Type I Induces Cell Viability and Migration via Nuclear Factor-κB/Vascular Endothelial Growth Factor Signaling Pathway in Colorectal Cancer - Wei, Rongfang; Zhong, Sixia; Qiao, Li; Guo, Mengjie; Shao, Miaomiao; Wang, Suyu; Jiang, Bin; Yang, Ye; Gu, Chunyan (Frontiers in Oncology, 2020)
Colorectal cancer (CRC) is a common malignant tumor of the digestive system. 5-alpha-reductase type I (SRD5A1), as an important part in the steroid metabolism, converts testosterone to dihydrotestosterone and regulates sex hormone levels, which accommodate tumor occurrence or development. However, the underlying molecular mechanism of SRD5A1 in CRC remains unclear. We compared SRD5A1 expression in CRC tissues with normal controls by immunohistochemistry and found that elevated SRD5A1 in CRC was relevant for poor patient prognosis. Furthermore, inducible downregulation of SRD5A1 by shRNA reduced cell viability, promoted cell cycle arrest and induced cell apoptosis and cellular senescence of CRC cells, as well as attenuated cell migration ability. In the followed experiments, we used dutasteride (an inhibitor of SRD5A1/2) to explore its inhibitory effect on the biological processes of CRC cells as mentioned above. Further mechanism study demonstrated that repression of SRD5A1 abolished the expression of p65 and vascular endothelial growth factor (VEGF), suggesting that SRD5A1 might regulate cell viability and migration through NF-κB/VEGF signaling pathway. Collectively, these findings implicate SRD5A1 acting as a novel biomarker for CRC diagnosis and prognosis, and provide compelling evidence for the future evaluation of dutasteride as a promising candidate for CRC treatment.